EVALUATION TECHNIQUES FOR LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS ( A STUDY AT SMK NEGERI 1 MOJOSONGO) - Insani, Zulaiha Nurul; Anshari, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research focuses on evaluating learning outcomes is an activity that is carried out after students have finished learning the material in a lesson. The implementation of this learning evaluation is used to assess something based on certain criteria through assessment. Each subject in the school will use learning evaluation to measure how far students have been able to understand the learning material that has been done, including the subject of Islamic Religious Education. Every subject teacher must have certain techniques in carrying out learning evaluation. These techniques are used on the basis of the student's ability and the teacher's intuition to the student. Data collection is carried out through interviews, document collection with an analytical approach that emphasizes qualitative description and understanding. The research results show that these techniques include objective tests in the form of true-false, multiple choice, matching and short answer tests. Meanwhile, subjective techniques use essay tests or long answers. This test trains students by giving answers based on what they understand and without any choice answers available. Usually this subjective test has a long answer.